Penyuluhan Tinjauan Multiperspektif untuk Percepatan Penurunan Stunting di Desa Bebatu, Kecamatan Sesayap Hilir Kabupaten Tana Tidung Provinsi Kalimantan Utara - Tri Astuti Sugiyatmi (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2024)
Stunting is a significant public health issue in Indonesia, including North Kalimantan. Stunting, which results from chronic malnutrition, affects not only physical growth but also has significant impacts on cognitive development. Stunting prevention is the most important in the first 1000 days from conception until age two. Stunting is not only about poor nutrition or health-related factors such as frequent infection and maternal health but also environmental factors such as improving access to clean water, hygiene, sanitation, socioeconomic factors like income and poverty, education, and cultural practice. This activity aimed to provide a multi-perspective and comprehensive overview of stunting as important information to decrease stunting in toddlers. The method was health education with lectures, discussions, and questions approaches. This activity was followed by all health cadres, mothers or caregivers of stunting babies or children, pregnant women, staff of the village, midwives, and staff from various sectors consisting of 50 people implemented on July 13, 2023, in Bebatu Village, Regency of Tana Tidung on North Kalimantan, Indonesia. This activity was successful marked by the enthusiasm of the participants and the many questions that came in during the questioning session. It is advised that complete health education-related materials be maintained for routine activities annually.